Test-Retest Measurement Invariance of the Nine-Item Internet Gaming Disorder Scale in Two Countries: A Preliminary Longitudinal Study. - Stavropoulos, Vasileios; Bamford, Luke; Beard, Charlotte; Gomez, Rapson; Griffiths, Mark D. (International Journal of Mental Health & Addiction, 2021)
The reliable longitudinal assessment of Internet Gaming Disorder (IGD) behaviors is viewed by many as a pivotal clinical and research priority. The present study is the first to examine the test-retest measurement invariance of IGD ratings, as assessed using the short-form nine-item Internet Gaming Disorder Scale (IGDS9-SF) over an approximate period of 3 months, across two normative national samples. Differences referring to the mode of the data collection (face-to-face [FtF] vs. online) were also considered. Two sequences of successive multiple group confirmatory factor analyses (CFAs) were calculated to longitudinally assess the psychometric properties of the IGDS9-SF using emergent adults, gamers from (i) the United States of America (USA; N = 120, 18–29 years, Mean = 22.35, 51.6% male) assessed online and; and (ii) Australia (N = 61, 18–31 years, Mean = 23.02, 75.4% male) assessed FtF. Configural invariance was established across both samples, and metric and scalar invariances were supported for the USA sample. Interestingly, only partial metric (factor loadings for Items 2 and 3 non-invariant) and partial scalar invariance (i.e., all thresholds of Items 1 and 2, and thresholds 1, 3, for Items 4, 6, 8, and 9 non-invariant) were established for the Australian sample. Findings are discussed in the light of using IGDS9-SF to assess and monitor IGD behaviors over time in both in clinical and non-clinical settings.